2012
DOI: 10.1130/g32652.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for widespread creep on the flanks of the Sea of Marmara transform basin from marine geophysical data

Abstract: aboard the R/V K. Piri Reis, which is operated by Dokuz Eylül University (Izmir, Turkey) (Fig. 1A). MCS data were acquired on a 450 m streamer in 2008, and on a 700 m or 1500 m streamer in 2010. The common midpoint (CMP) spacing was 3.125 m, streamer depth was 3-4 m, and ABSTRACT"Wave" fi elds have long been recognized in marine sediments on the fl anks of basins and oceans in both tectonically active and inactive environments. The origin of "waves" (hereafter called undulations) is controversial; competing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
2
45
0
2
Order By: Relevance
“…More recently, a detailed analysis of these undulations, based on high resolution seismic data, concluded that these sediment waves correspond to slow gravity-driven downslope creep (Shillington et al, 2012).…”
Section: Morpho-sedimentary Contextmentioning
confidence: 97%
See 2 more Smart Citations
“…More recently, a detailed analysis of these undulations, based on high resolution seismic data, concluded that these sediment waves correspond to slow gravity-driven downslope creep (Shillington et al, 2012).…”
Section: Morpho-sedimentary Contextmentioning
confidence: 97%
“…Numerous studies of the seafloor morphology of the Sea of Marmara identified sediment waves (Okay et al, 1999;Imren et al, 2001 andShillington et al, 2012) and mass wasting features (e.g. Gazioğlu et al, 2002;Altinok et al, 2003;Gazioğlu et al, 2005;Gökçeoğlu et al, 2009;Görür and Çağatay, 2010;Özeren et al, 2010).…”
Section: Morpho-sedimentary Contextmentioning
confidence: 98%
See 1 more Smart Citation
“…Two morphological features that could be the result of the interaction of slope instability with other processes (such as bottom currents or fluid escapes) were further identified along the Owen Ridge: undulating (Lee et al, 1981;Field and Barber, 1993;Baraza and Ercilla, 1996;Gardner et al, 1999;Corregiari et al, 2001;Lee et al, 2002), or as the result of a combination of deformation and depositional processes Gonthier et al, 2002;Shillington et al, 2012). Sub-circular depressions similar to the ones observed along the Owen Ridge are described on the Malpelo Ridge (Lonsdale and Fornari, 1980) and on the Carnegie Ridge (Michaud et al, 2005) in the Pacific Ocean.…”
Section: Potentially Multi-processes Generated Featuresmentioning
confidence: 86%
“…The different results concern (1) deep fluids expulsion related to seismotectonic activity (Géli et al, 2008;Tary et al, 2012;Burnard et al, 2012, etc. ); (2) mass wasting and creep (Zitter et al, 2012;Shillington et al, 2012); (3) deep sedimentation specificities Sari and Çagatay, 2006;Çagatay et al, 2012;Drab et al, 2012); and (4) detection and dating of historical coseismic scarps (Armijo et al, 2005;Uçarkuş, 2010). Historical tsunami reports and modeling (Altinok et al, 2011;Hébert et al, 2005) complete these different data, taking into account the fact that these phenomena are not systematically associated with Armijo et al (2002Armijo et al ( , 2005, and GPS kinematics from McClusky et al (2000) and Reilinger et al (2006).…”
Section: Structural Setting and Recent Seismic Activitymentioning
confidence: 99%